2009
DOI: 10.1001/jama.2009.377
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Care for Chronic Pain in Primary Care

Abstract: HRONIC NONCANCER PAIN IS associated with considerable physical and psychosocial impairment, distress, comorbid depression, and increased health care use and costs. [1][2][3][4] Many primary care patients report chronic pain, 2,5,6 most commonly musculoskeletal pain. 2,7 Guidelines for chronic pain treatment have been developed. 8,9 However, implementation has been problematic, especially in busy primary care practices in which access to recommended treatment components may be limited.Multifaceted, collaborativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
268
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(293 citation statements)
references
References 56 publications
8
268
0
3
Order By: Relevance
“…Study design, participant inclusion, and main results have been reported in detail elsewhere [31][32]. The study took place in three urban and two rural primary care clinics of a VA medical center in the Pacific Northwest.…”
Section: Methodsmentioning
confidence: 99%
“…Study design, participant inclusion, and main results have been reported in detail elsewhere [31][32]. The study took place in three urban and two rural primary care clinics of a VA medical center in the Pacific Northwest.…”
Section: Methodsmentioning
confidence: 99%
“…As part of the safety assessment, appropriate opioid prescribing should include consideration of potential interactions with coprescribed medications, including other controlled substances such as benzodiazepines, alcohol, and illicit substances. With respect to enhancing efficacy, consensus guidelines and a growing body of evidence 8,9 support multi-modal pain treatment. Opioid therapy is optimal when provided along with education to promote patient self-efficacy and self-care, and evidence-based psychological and rehabilitation therapies.…”
Section: Characterizing Appropriate Ongoing Opioid Prescribing: Shiftmentioning
confidence: 99%
“…Collaborative care has also been shown to be efficacious in reducing pain severity and painrelated disability and depression among chronic patients. 12 The foreseeable effects of collaborative care management in primary care are substantial: collaborative care has the potential to reduce the global burden of depression-related illness overall, as well as improve population-level well-being. 5 But to reap the optimal benefits from this type of arrangement, it is critical that the primary care and mental health care cultures-using a common treatment approach-integrate over time.…”
Section: Introductionmentioning
confidence: 99%